An effective heuristic for no-wait flow shop production to minimize makespan. (July 2016) - Ye, Honghan; Li, Wei; Miao, Enming
Abstract: In no-wait flow shop production, each job must be processed without any interruption from its start time on the first machine to its completion time on the last machine. To minimize makespan in no-wait flow shop production is one of the main concerns in industry. In this paper, we propose an average departure time (ADT) heuristic for minimizing makespan in no-wait flow shop production. Based on the computational experiment with a large number of instances of various sizes, the ADT heuristic performs better than three existing best-known heuristics in the same computational complexity environment.